2009
DOI: 10.1016/j.dnarep.2008.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of specialized DNA polymerases in mutagenesis by 8-hydroxy-dGTP in human cells

Abstract: In contrast, the knock-down of DNA polymerase ι did not affect the 8-OH-dGTP-induced mutations. The decrease in the induced mutation frequency was more evident by double knock-downs of DNA pols η plus ζ and REV1 plus DNA pol ζ (but not by that of DNA pol η plus REV1),suggesting that REV1-DNA pol η and DNA pol ζ work in different steps.These results indicate that specialized DNA polymerases are involved in the mutagenesis induced by the oxidized dGTP.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 52 publications
1
54
3
Order By: Relevance
“…Previously, we reported that A:T → C:G transversions were specifically induced by 8-oxo-dGTP in mammalian cells [48,51]. In this study, we examined the mutagenic potential of 8-oxo-dGTP in cells with knocked-down DNA glycosylases.…”
Section: Decrease In 8-oxo-dgtp-induced Mutations By Knock-down Of Mutyhmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that A:T → C:G transversions were specifically induced by 8-oxo-dGTP in mammalian cells [48,51]. In this study, we examined the mutagenic potential of 8-oxo-dGTP in cells with knocked-down DNA glycosylases.…”
Section: Decrease In 8-oxo-dgtp-induced Mutations By Knock-down Of Mutyhmentioning
confidence: 99%
“…where G* represents 8-oxo-Gua. The ss form of pZ189-StuI [48] was obtained as described [17]. The oligodeoxyribonucleotides were annealed with the ss form of pZ189-StuI, and the double-stranded (ds) DNAs containing 8-oxo-Gua were obtained as described previously [49].…”
Section: Construction Of Shuttle Plasmids Containing 8-oxo-guamentioning
confidence: 99%
See 1 more Smart Citation
“…Pursell et al demonstrated that the concentration of 8-OH-dGTP was 1-10% of that of unmodified dGTP in the mitochondrial nucleotide pool [18]. 8-OH-dGTP is mutagenic and specifically induced A:TC:G transversions in living bacterial and mammalian cells [19][20][21]. The A:TC:G mutations seem to be triggered by the incorporation of 8-OH-dGTP opposite A in template DNA, resulting in the formation of 8-OH-Gua:A base pairs, and the subsequent incorporation of dCTP opposite 8-OH-Gua during the next round of replication would cause the transversion [22].…”
Section: -Oh-gua Is Highly Mutagenic and Induces G:ct:a Transversiomentioning
confidence: 99%
“…We recently found that the knock-downs of DNA pols η and ζ, and REV1 reduced the frequency of A:TC:G mutations induced by exogenous 8-OH-dGTP [21], suggesting that these proteins are involved in the mutagenesis induced by 8-OH-dGTP. This result raised the question of whether these DNA pols contribute to the incorporation of 8-OH-dGTP and/or to the insertion of dCTP opposite 8-OH-Gua.…”
Section: -Oh-gua Is Highly Mutagenic and Induces G:ct:a Transversiomentioning
confidence: 99%